Excavation Results from Gua Bedug: New Insights on the Early-Mid Holocene Prehistory of the Rembang Zone - Wibowo, Hari; Citra Iqliyah, Darojah; Purnamasari, Rizka; Aris Tanudirjo, Daud; Noerwidi, Sofwan; Rahmadi, Cahyo (Badan Riset dan Inovasi Nasional (BRIN), 2024)
There are not many Early-Mid Holocene sites in the Rembang Zone, moreover that have human remains recovered from excavation. Gua Bedug is one of these sites, and this article presents the preliminary analysis of its excavation results. Currently, dating associated with human remains from Gua Bedug shows occupation from 5.895 - 8.542 cal. BP, showing similarity with the human remains from the southern part of Java that ranged between 9.000-5.000 BP. These human remains at Gua Bedug were recovered in context mostly with shell and bone artifacts, markers of Preneolithic culture. Dating related to the Preneolithic cultural layers in Gunung Sewu shows that this culture lasted between 12,000 to 4,000 BP. Therefore, the cultural layers from the southern part of Java are older than the northern part. Although they share the same markers of Preneolithic culture as the southern sites, the much smaller quantity of lithic artifacts from Gua Bedug, and the abundance of shell and bone artifacts is more likely driven by local adaptation rather than material preference for specific purposes. This local adaptation is also shown in the faunal remains records, which indicate a close interaction between the people of Gua Bedug and their aquatic paleoenvironment.